1998
DOI: 10.1128/jcm.36.6.1683-1687.1998
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Bacteria in Blood of Typhoid Fever Patients and Relationship between Counts and Clinical Features, Transmissibility, and Antibiotic Resistance

Abstract: Salmonella typhi was isolated from 369 andSalmonella paratyphi A was isolated from 6 of 515 Vietnamese patients with suspected enteric fever. Compared with conventional broth culture of blood, direct plating of the buffy coat had a diagnostic sensitivity of 99.5% (95% confidence interval [CI], 97.1 to 100%). Blood bacterial counts were estimated by the pour plate method. The median S. typhi count in blood was 1 CFU/ml (range, <0.3 to 387 CFU/ml), of which a mean of 63% (95% CI, 58 to 67%) were intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(135 citation statements)
references
References 24 publications
2
124
1
Order By: Relevance
“…They were able to amplify fliC from all culture-positive and negative blood samples tested but reported a higher gene copy number in culture positives (1,000 -45,000), compared to negatives (<1000). However, this real-time PCR data is somewhat contradictory with the microbiological data, which demonstrates that bacteria/ml of blood is generally low with the majority of patients having <1 organism/ml of blood [21]. It is somewhat surprising that typhoid patients may have between a 1,000 to 45,000 times more dead bacteria than live bacteria in the blood.…”
Section: The Limits Of Dna Detectionmentioning
confidence: 79%
See 1 more Smart Citation
“…They were able to amplify fliC from all culture-positive and negative blood samples tested but reported a higher gene copy number in culture positives (1,000 -45,000), compared to negatives (<1000). However, this real-time PCR data is somewhat contradictory with the microbiological data, which demonstrates that bacteria/ml of blood is generally low with the majority of patients having <1 organism/ml of blood [21]. It is somewhat surprising that typhoid patients may have between a 1,000 to 45,000 times more dead bacteria than live bacteria in the blood.…”
Section: The Limits Of Dna Detectionmentioning
confidence: 79%
“…This situation may be exacerbated as many patients reach microbiological facilities at a later stage of infection or may be "self treated" with antimicrobials. Thus, there are a number of characteristics of the pathogenesis of typhoid that impinge on diagnostics [21,22]. An obvious caveat is the low number of bacteria in the blood and other tissues.…”
Section: Typhoid Infectionsmentioning
confidence: 99%
“…One of the ways that S. enterica spreads within the host is through the bloodstream. 12,25,55,56 Improvements in bacterial uptake could reduce the levels of bacteria in the circulating blood and hence possibly limit the spread of the bacteria in vivo and prevent or stop bacteraemia in septicaemic infections. Studies on the distribution of IgG antibody subclasses in human immune serum in areas of endemic typhoid fever have shown that the dominating IgG antibody subclass is IgG2.…”
Section: Discussionmentioning
confidence: 99%
“…Among studies which considered the unselected group, only 2 ⁄ 6 report prevalences >1%, with 5.51% prevalence in Dhaka, Bangladesh and 6.1% in Malaysia (Choo et al 1993;Sinha et al 1999;Feng 2000;Brooks et al 2005;Siddiqui et al 2006). In studies on selected populations, the reported prevalence was between 8.6% and 71.5% (Wain et al 1998;Vollaard et al 2004). The high figures in this group may be attributed to highly restricted inclusion criteria.…”
Section: Prevalence Of Typhoidmentioning
confidence: 99%